2022
DOI: 10.3389/fonc.2022.815998
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 is regulated by DEPDC1 to facilitate development and metastasis of oral squamous cell carcinoma

Abstract: The Disheveled, EGL-10, Pleckstrin domain containing 1 (DEPDC1) is a new oncogene that has recently been described. The mechanisms and functions of its expression are yet to be determined in oral squamous cell carcinoma (OSCC). In the present study, the impact of DEPDC1 on the growth and development of OSCC was investigated using animal models, cell lines and human tissue samples. Elevated DEPDC1 expression within cancer cell lines and human OSCC has been identified. Mechanistic examination showed that restore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The expression of DEPDC1 in TC tissue was observed in the cytoplasm, as shown in Figure 2, according to The Human Protein Expression Atlas (THPA, https://www.proteinatlas.org/). Studies have shown that DEPDC1 is involved in the occurrence and development of various cancers, but there is currently a lack of in-depth research specifically on TC [9][10][11][12].…”
Section: Preliminary Screening Of Candidate Key Genes Using Wgcnamentioning
confidence: 99%
“…The expression of DEPDC1 in TC tissue was observed in the cytoplasm, as shown in Figure 2, according to The Human Protein Expression Atlas (THPA, https://www.proteinatlas.org/). Studies have shown that DEPDC1 is involved in the occurrence and development of various cancers, but there is currently a lack of in-depth research specifically on TC [9][10][11][12].…”
Section: Preliminary Screening Of Candidate Key Genes Using Wgcnamentioning
confidence: 99%